Preservice Teachers’ Practices and Perceptions of ICT Integration in English Language Teaching (SNPRC Journal, 2025)
The integration of Information and Communication Technology (ICT) has become increasingly vital in education, offering multimodal learning opportunities and enhancing both content knowledge and pedagogy. This study explored the practices and perceptions of preservice English language teachers in using ICT while pursuing postgraduate degrees in English education at two constituent campuses (of two universities)in semiurban areas of Nepal. Guided by an interpretative phenomenological design, data were collected through semi-structured interviews with ten purposefully selected participants. Thematic analysis of data revealed that preservice English language teachers used ICT tools in learning and enhancing their prospective teaching profession. Despite infrastructural challenges, ICT promoted their autonomy and attention towards learning content. It also fostered their curiosity, motivation, and engagement for attaining professional skills. The study highlights the need for institutional support and training to maximize its pedagogical potential in the English language teaching context of Nepal.